ASUHAN KEBIDANAN KEHAMILAN PADA NY. N DENGAN MULTIGRAVIDA USIA TUA DI KLINIK PERMATA NABILA KOTA SERANG TAHUN 2019 - Evi Avicenna Agustin; Oktavia Puspa Kandi (Journal Of Applied Health Research And Development, 2019)
Pregnancy with old age multigravida is one of the complications of pregnancy and is a contributing factor for MMR in Indonesia. Throughout 2015, 25% of AKI cases in Indonesia were found to be caused by old age pregnancy. In the Permata Nabila Clinic in 2018 out of 88 pregnant women who examined their pregnancies found 22 cases with multigravida pregnancies in old age. The purpose of this Case Study is to be able to provide midwifery care for pregnant women with multigravida in old age at the Permata Nabila Clinic in 2019. This study uses qualitative types, using primary and secondary data. After the assessment, it was found that Ny. N with old age multigravida. Then Ny.N is given midwifery care that is given includes care provided includes: providing nutritional counseling, providing counseling about the risk of multigravida pregnancy in old age, providing counseling about danger signs TM III, giving mother Fe therapy 1x1 a day and calc 1x1 a day. And expected This case study can provide the best service to pregnant women with multigravida in old age.